Intraperitoneal Injection of Multiplacentas Pooled Cells Treatment on a Mouse Model with Aplastic Anemia. (22nd February 2016) - Li, Jun; Chen, Hong; Lv, Yan-Bo; Wang, Qiang; Xie, Zheng-Jun; Ma, Li-Hua; He, Jie; Xue, Wei; Yu, Shan; Guo, Jun; Wang, Ting-Hua; Wu, Tian-Xi; et al.
Abstract : Coinfusion of hematopoietic and mesenchymal stem cells is more effective than hematopoietic stem cell transplantation alone. It is necessary to explore a safe and routine mixed stem cell intraperitoneal transplantation method. Multiplacentas pooled cells were intraperitoneally injected into a radiation- and immunity-induced mouse aplastic anemia model with single time. Then, mouse survival time, peripheral blood hemoglobin count, bone marrow architecture, and donor cell engraftment were assessed. The recipient mouse exhibited donor cell engraftment in both bone marrow and peripheral blood. Survival time and peripheral blood hemoglobin count increased in placenta pooled cells treated mice, compared with model-only controls (P = 0.048 andP = 0 . 000, resp.). However, placentas pooled cells failed to cause a significant decrease in bone marrow pimelosis area (P = 0.357 ). Intraperitoneally transplanted multiplacentas pooled cells can survive and engraft into a host body through blood circulation, which can increase the life span of an aplastic anemia model mice, and delay but not abrogate the development of aplastic anemia. Furthermore, they appear to play a role in increasing peripheral blood hemoglobin level response for increasing the life span of aplastic anemia model mice.